1996
DOI: 10.1111/j.1365-2885.1996.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory, endocrine and metabolic changes in ponies undergoing intravenous or inhalation anaesthesia

Abstract: Six Welsh gelding ponies (weight 246 +/- 6 kg) were premedicated with 0.03 mg/kg of acepromazine intravenously (i.v.) followed by 0.02 mg/kg of detomidine i.v. Anaesthesia was induced with 2 mg/kg of ketamine i.v. Ponies were intubated and lay in left lateral recumbency. On one occasion anaesthesia was maintained for 2 h using 1.2% halothane in oxygen. The same group of ponies were anaesthetized 1 month later using the same induction regime and anaesthesia was maintained with a combination of detomidine, ketam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 17 publications
11
58
0
3
Order By: Relevance
“…However, if ACTH concentrations increase but 11-deoxycortisol remains low, primary adrenocortical dysfunction is implied. Measurement of 11-deoxycortisol is described in the horse,31 but commercial assays are not readily available in all clinical settings, and many assays require a cumbersome extraction step. Furthermore, while intravenous infusions of metyrapone have been described in horses,32 oral metyrapone has not been used for HPA axis function assessment in ill horses to date.…”
Section: Methods For Diagnosis Of Adrenocortical Insufficiencymentioning
confidence: 99%
“…However, if ACTH concentrations increase but 11-deoxycortisol remains low, primary adrenocortical dysfunction is implied. Measurement of 11-deoxycortisol is described in the horse,31 but commercial assays are not readily available in all clinical settings, and many assays require a cumbersome extraction step. Furthermore, while intravenous infusions of metyrapone have been described in horses,32 oral metyrapone has not been used for HPA axis function assessment in ill horses to date.…”
Section: Methods For Diagnosis Of Adrenocortical Insufficiencymentioning
confidence: 99%
“…Several TIVA protocols have been reported to provide adequate analgesia with preservation of cardiovascular function and arterial oxygenation [47,52,[58][59][60][61]. Two studies demonstrated that the TIVA protocol used provided superior arterial blood pressure values compared with halothane [62,63]. These TIVA studies were performed on healthy individuals, and supplemental oxygen, with or without controlled ventilation, was provided.…”
Section: Anesthetic Induction and Maintenancementioning
confidence: 99%
“…Gesunde anästhesierte Pferden zeigen bei Einleitung Laktatkonzentrationen von 1,4 mmol/l, welche nach 2,5 Stunden Allgemeinanästhesie auf 2,1 mmol/l ansteigen (Boscan et al 2007 (Luna et al 1996), anaerober Metabolismus durch Hypoxie, erniedrigter Laktatstoffwechsel sowie ein Überschuss von Laktatadministration durch die Verabreichung von 10 ml/kg/h RL über die Anästhesiezeit von 2,5 Stunden (Boscan et al 2007). Bei Hunden mit Lymphom wurde gezeigt, dass nach Verabreichung von RL ein transienter Laktatanstieg ausgelöst wird, der sich zwei Stunden nach Infusionsende normalisiert (Vail et al 1990).…”
Section: Ergebnisseunclassified